Transition with Purpose Pathways from English Language to Academic Study - Miller, Michele; Greenhoe, Anne (Open textbook library., 2018)
This Open Access Textbook will guide students through their English language to academic degree studies. Part one of this textbook is a guide for moving from ESL study to academic study at Portland State University. It includes the resources students will use to understand policies and processes governing their degree study and their transition to academic coursework. Part two focuses on how academic skills are used across various disciplines and is comprised of activities and assignments designed to practice these skills. Key elements include culture and expectations in an American university, transferring academic skills from ESL to content-specific academic courses, and helpful exercises to be academically successful.